2021
DOI: 10.3390/su13094789
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Residents’ Participation on Their Support for Tourism Development at a Community Level Destination

Abstract: Resident participation is crucial to the success of tourism development at community-level destinations. This study examines the effect of residents’ participation on their support for tourism development at the community level through a case study of Gamcheon Culture Village, South Korea. Using the structural equation model (SEM), including the variables of participation of tourism development, community attachment, economic dependence, perceived positive impacts, perceived negative impacts, and attitude towa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 55 publications
(90 reference statements)
5
10
1
2
Order By: Relevance
“…Additionally, the final dataset of 344 is consistent with practices from prior studies; for instance, Kim et al [11] examined 189 residents; Moghavvemi et al [45] investigated a sample of 333 residents; Wang et al [57] validated their model based on 294 respondents; Yu et al [13] based their model on 322 respondents; Jeon et al [52] evaluated the proposed model based on a sample of 347 respondents; Chen and Chen [50] examined 239 respondents; Huong and Lee [39] analyzed 267 responses; Zhang et al [40] considered a sample of 297 respondents.…”
Section: Data Collectionsupporting
confidence: 63%
See 4 more Smart Citations
“…Additionally, the final dataset of 344 is consistent with practices from prior studies; for instance, Kim et al [11] examined 189 residents; Moghavvemi et al [45] investigated a sample of 333 residents; Wang et al [57] validated their model based on 294 respondents; Yu et al [13] based their model on 322 respondents; Jeon et al [52] evaluated the proposed model based on a sample of 347 respondents; Chen and Chen [50] examined 239 respondents; Huong and Lee [39] analyzed 267 responses; Zhang et al [40] considered a sample of 297 respondents.…”
Section: Data Collectionsupporting
confidence: 63%
“…Local communities may withdraw their support for sustainable tourism development if they understand that the expenses of tourism may exceed the benefits [57]. Previous studies [1,4,8,11,13,17,42,47] confirmed the interrelationships between residents' perceived benefits and costs of tourism and their support for sustainable tourism activities. Thus, the more positively and favorably the benefits of tourism were viewed by the local people, the greater their support for tourism development; conversely, the less favorable the impacts of tourism, the less supportive the host population were in terms of enhancing tourism in a particular area.…”
Section: Residents' Support For Sustainable Tourism Development and Tourism Impactsmentioning
confidence: 90%
See 3 more Smart Citations